MTOR pathway and somatostatin receptors expression intratumor-heterogeneity in ileal NETs. Issue 7 (10th June 2021) - Borga, Chiara; Dal Pozzo, Carlo Alberto; Trevellin, Elisabetta; Bergamo, Francesca; Murgioni, Sabina; Milanetto, Anna Caterina; Pasquali, Claudio; Cillo, Umberto; Munari, Giada; Martini, Chiara; De Carlo, Eugenio; Zagonel, Vittorina; et al.
Abstract : The knowledge of the molecular landscape of ileal neuroendocrine tumors (NETs) is affected by the lack of systematic studies investigating intra-tumoral heterogeneity. In this study, intra-tumoral heterogeneity was investigated in 27 primary ileal G1-NETs and their matched nodal and liver metastases in order to assess the tumor grading, the expression status of two somatostatin receptor isoforms (i.e. SSTR2A and SSTR5) and mTOR signaling dysregulation (ph-mTOR, ph-p70S6K, ph-4EBP1, PTEN and miR-21). Among the 27 G1 primary tumors, 4 shifted to G2 in the matched liver metastasis. Although mTOR activation was pretty consistent between primary and secondary malignancies, mTOR effectors (ph-p70S6K and ph-4EBP1) were overexpressed in matched liver metastases, whereas PTEN expression profile changed in only two cases. MiR-21 was significantly up-regulated in the metastatic setting. Although SSTRs expression was present in most of the primary tumors and matched metastasis, we found SSTR5 expression to be significantly increased in liver metastases. Notably, SSTRs expression was heterogeneous within the same lesions in most of the lesions. Overall, despite primary and metastatic ileal NETs show a similar molecular landscape, tumor grading and mTOR signaling pathway may diverge in the metastatic setting, thus affecting prognosis and treatment.